The Development of the Archerys Instructional Design Model Arcs-Motivational-Based in Efforts to Reduce Academic Dishonesty in Higher Education - Darmansyah, Darmansyah; Darman, Regina Ade (PPSDP International Journal of Education, 2024)
Cheating rate academic becomes problems that arise in various world campus. Lots of research disclose has occur enhancement level fraud academic. Enhancement dishonesty that precisely the more tall when use technology information and communication the more extends. Dishonesty academic in college tall is problem bad affect institution learning in many countries around the world. There are many possible explanations and theories explain how dishonesty academic the more difficult dammed. Device increasingly technology advanced open encouraging opportunity happening fraud academic. Effort resolve academic dishonesty too many offered , however still little to talk about about effort prevention through design model design instructional , learning processes and forms evaluation. The aim of this study is to develop design models instructional latest for resolve dishonesty academic in learning. This model rooted in ARCS-Motivational with name Archery’s Instructional Design Model developed through integration of morals and ethics in every step learning use technique evaluation extenics. Results of the development of the design model instructional this stated Validand effective to increase motivation study as well as reduce dishonesty academic levels. Deeper and broader testing will have more convincing that this model instructional design will develop through research continued in the future.